The influence of dust originating from carbon black nanopowders on the explosion characteristics of lean methane/air mixtures within a turbulent environment. (September 2018) - Kylafis, Georgios F.; Tomlin, Alison S.; Sleigh, P. Andrew; Lawes, Malcolm; Vignes, Alexis
Abstract: Industrial requirements present some unique challenges that can be met only by the application of engineered nanomaterials (ENMs). The completion of risk assessments based on the knowledge of the change in the explosion severity of turbulent gas/air mixtures caused by the accidental dispersion of nanopowders is vital before integrating such materials into existing systems. In this work, known amounts of selected carbon black nanopowders were mixed with methane near the lower-flammability-limit (LFL) to form hybrid mixtures of variable dust concentration. Mixtures were ignited in a 23 L cylindrical combustion vessel that allowed the control of isotropic turbulence through specially designed fans. The particle size distribution, the explosion pressure history and the flame speed derived from high speed Schlieren cine photographs, were measured. The influence of dispersed amounts of nanopowders on explosion severity was investigated by comparing the results with those obtained for pure methane-air explosions. Results indicated that the release of a relatively low mass of nanopowder into methane-air mixtures resulted in a more severe explosion than that of a higher amount. Also, despite the very low content of volatiles in the selected nanopowders, a hybrid mixture can be ignitable at an equivalence ratio well below the LFL of the gas. However this ignitability was shown to be related to the agglomeration state of powder in the dispersion phase, indicating that as the mean particle size decreases, a hybrid mixture with an extremely low content of flammable gas could be ignitable. From a risk assessment point of view, these results may have great significance for specific industrial processes aiming to utilise ENMs. Highlights: The influence of carbon blacks nanopowder addition to lean turbulent methane-air mixture explosions. Heterogeneous mixtures were ignited more violently compared to their respective homogenous mixtures. The release of a low mass of nanopowder into methane-air resulted in a more severe explosion than that of a higher amount. Heterogeneous mixtures were ignitable at an equivalence ratio well below the lower flammability limit of the gas. As the mean particle size decreases, a hybrid mixture of an extremely low content of gas could be ignitable.